2022
DOI: 10.3390/nu14183707
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ulcerative Colitis by Aspartate via RIPK Pathway Modulation and Gut Microbiota Composition in Mice

Abstract: The intestine requires a great deal of energy to maintain its health and function; thus, energy deficits in the intestinal mucosa may lead to intestinal damage. Aspartate (Asp) is an essential energy source in the intestinal mucosa and plays a vital part in gut health. In the current study, we hypothesized that dietary supplementation of Asp could alleviate DSS-induced colitis via improvement in the colonic morphology, oxidative stress, cell apoptosis, and microbiota composition in a mouse model of dextran. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Moreover, the standard error of the medium dose of TSCHs (500 mg kg −1 ) was relatively large, which may be caused by individual differences in animals. Such a result was similar to that reported by Wang et al 60 and Hu et al 61 It is suggested that TSCHs may inhibit the activation of inflammatory signaling pathways associated with IL-6 to reduce the production of IL-6, sequentially attenuating intestinal mucosal damage and IL-6 cytokine release.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the standard error of the medium dose of TSCHs (500 mg kg −1 ) was relatively large, which may be caused by individual differences in animals. Such a result was similar to that reported by Wang et al 60 and Hu et al 61 It is suggested that TSCHs may inhibit the activation of inflammatory signaling pathways associated with IL-6 to reduce the production of IL-6, sequentially attenuating intestinal mucosal damage and IL-6 cytokine release.…”
Section: Discussionsupporting
confidence: 90%
“…Such a result was similar to that reported by Wang et al 60 . and Hu et al 61 . It is suggested that TSCHs may inhibit the activation of inflammatory signaling pathways associated with IL‐6 to reduce the production of IL‐6, sequentially attenuating intestinal mucosal damage and IL‐6 cytokine release.…”
Section: Discussionsupporting
confidence: 90%
“…31,32 Mice de cient in GPX2 exhibit increased susceptibility to experimentally-induced colitis, while overexpression confers protection, suggesting a critical role for GPX2 in maintaining intestinal homeostasis. 32,33 Interestingly, our results indicate that genetically-elevated GPX2 expression is associated with increased ulcerative colitis risk, potentially due to disruption of redox homeostasis or compensatory upregulation in the in amed mucosa. 34 These ndings suggest that selectively modulating GPX2 activity may represent a novel therapeutic strategy for ulcerative colitis.…”
Section: Discussionmentioning
confidence: 69%
“…Previous study found increased Odoribacter in fecal microbiota transplantation-treated colitis mice ( Zhang et al, 2020 ), which was in line with LPS-induced mice, and higher concentration treatment of BLBP depicted a higher abundance of Odoribacter in mice in group GE ( p < 0.01). Lactobacillus is a commonly recognized genus of probiotics, which can maintain the intestinal barrier and provide protection against inflammation ( Bai et al, 2022 ), and a lower abundance of Lactobacillus had been found in antibiotic-associated diarrhea in mice ( Chen C. et al, 2022 ) and ulcerative colitis mice ( Hu et al, 2022 ). In the current study, a higher abundance of Lactobacillus was detected in mice in all BLBP-supplemented groups, especially in group GC and GE, which was in accordance with Lycium barbarum arabinogalactan treated mice with colitis ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%